Reproductive Performance of Friesian Holstein Crossbred Dairy Cattle after A Foot-And-Mouth Disease Outbreak in Lembang, Indonesia - Pamungkas, Hanunghanindito; Septiyani, Septiyani; Solihati, Nurcholidah (Jurnal Ilmu Ternak Universitas Padjadjaran, 2026)
Foot-and-mouth disease (FMD) is a highly contagious viral disease that may impair reproductive efficiency in dairy cattle. This study aimed to evaluate changes in the reproductive performance of Friesian Holstein crossbred dairy cows following an FMD outbreak at UPTD BPTSP and HPT Cikole, Lembang, West Java, Indonesia. A retrospective study was conducted using reproductive records collected from 2019 to 2023. The reproductive parameters analyzed were calving interval, service per conception, conception rate, service period, and first mating postpartum. Differences between the pre- and post-FMD periods were assessed using paired sample t-tests. The results showed significant differences in calving interval, service per conception, conception rate, and first mating postpartum between the two periods (P<0.05), whereas service period did not differ significantly (P=0.882). Among these parameters, conception rate showed a marked decline from 92.30% before the outbreak to 63.54% after the outbreak (P=0.001). Overall, the post-FMD period was associated with poorer reproductive performance in the studied herd. These findings suggest that the FMD outbreak was followed by reduced reproductive efficiency, particularly in calving interval, service per conception, conception rate, and first mating postpartum.